Pengaruh Pelatihan Kerja terhadap Kinerja Karyawan dengan Kompetensi Karyawan Sebagai Variabel Mediasi pada Departemen Produksi pada Salah Satu Perusahaan Tambang di Indonesia - Hamid, Muhammad Nawal; Alexandri, Mohammad Benny; Purnomo, Margo (Universitas Batanghari, 2024)
This study aims to analyze the impact of job training on employee performance, with employee competency serving as a mediating variable. This quantitative research collected data through questionnaires. The respondents comprised 202 employees from the production department of PT XYZ, selected using proportional stratified random sampling. Data processing employed Structural Equation Modeling Partial Least Squares (SEM PLS), incorporating convergent validity tests, discriminant validity tests, and composite reliability tests. The analysis techniques included path coefficient analysis, R-square testing, bootstrapping, and specific indirect effect testing. The findings of this study are: (1) job training has a significant effect on employee performance; (2) job training significantly influences employee competency; (3) competency significantly impacts employee performance; and (4) competency significantly mediates the effect of job training on employee performance. This research provides new insights into the mediating role of employee competency in the relationship between job training and employee performance within the context of an mining industry. The study contributes to the body of knowledge by highlighting the importance of competency development through job training to enhance employee performance. It offers practical implications for human resource practices in similar industrial settings, emphasizing the critical role of competency as a mediator.